2021
DOI: 10.1038/s41598-020-79624-0
|View full text |Cite
|
Sign up to set email alerts
|

Ascending dorsal column sensory neurons respond to spinal cord injury and downregulate genes related to lipid metabolism

Abstract: Regeneration failure after spinal cord injury (SCI) results in part from the lack of a pro-regenerative response in injured neurons, but the response to SCI has not been examined specifically in injured sensory neurons. Using RNA sequencing of dorsal root ganglion, we determined that thoracic SCI elicits a transcriptional response distinct from sciatic nerve injury (SNI). Both SNI and SCI induced upregulation of ATF3 and Jun, yet this response failed to promote growth in sensory neurons after SCI. RNA sequenci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 90 publications
2
17
0
Order By: Relevance
“…In neurons, axonal PPARγ contributes to the pro-regenerative response after axon injury (Lezana et al, 2016) and our recent study suggest that FASN may generate ligands for PPARγ in neurons (Ewan et al, 2021). We recently demonstrated that in SGC, FASN is required for the activation of PPARα and that PPARα signaling promote axon regeneration in adult peripheral nerves (Avraham et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In neurons, axonal PPARγ contributes to the pro-regenerative response after axon injury (Lezana et al, 2016) and our recent study suggest that FASN may generate ligands for PPARγ in neurons (Ewan et al, 2021). We recently demonstrated that in SGC, FASN is required for the activation of PPARα and that PPARα signaling promote axon regeneration in adult peripheral nerves (Avraham et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, dorsal root injury causes up-regulation of the pro-regenerative gene Atf3 (Huang et al, 2006), but only in large diameter neurons, whereas Atf3 and Jun are upregulated in a majority of neurons after 4 peripheral nerve injury (Chandran et al, 2016;Renthal et al, 2020;Seijffers et al, 2007;Tsujino et al, 2000). Spinal cord injury also leads to activation of Atf3 in large diameter neurons, but this is not sufficient to promote regenerative growth (Ewan et al, 2021). Another possibility explaining the slow growth capacity of axons in the injured dorsal root is the contribution of non-neuronal cells.…”
Section: Introductionmentioning
confidence: 99%
“…In neurons, axonal PPARγ contributes to the pro-regenerative response after axon injury ( Lezana et al, 2016 ) and our recent study suggest that FASN may generate ligands for PPARγ in neurons ( Ewan et al, 2021 ). We recently demonstrated that in SGC, FASN is required for the activation of PPARα and that PPARα signaling promote axon regeneration in adult peripheral nerves ( Avraham et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, dorsal root injury causes up-regulation of the pro-regenerative gene Atf3 ( Huang et al, 2006 ), but only in large diameter neurons, whereas Atf3 and Jun are upregulated in a majority of neurons after peripheral nerve injury ( Chandran et al, 2016 ; Renthal et al, 2020 ; Seijffers et al, 2007 ; Tsujino et al, 2000 ). Spinal cord injury also leads to activation of Atf3 in large diameter neurons, but this is not sufficient to promote regenerative growth ( Ewan et al, 2021 ). Another possibility explaining the slow growth capacity of axons in the injured dorsal root is the contribution of non-neuronal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Axon regeneration failure causes long term structural and functional impairment after a variety of CNS trauma including brain and spinal cord injury (SCI) [ 14 , 15 ]. Previous work has demonstrated that accumulation of certain lipids and dysregulation of lipid metabolism not only contribute to developmental disorders [ 16 , 17 ], axon growth and regeneration failure after CNS trauma [ 6 , 18 ], but also neurodegenerative diseases [ 19 , 20 ]. Lipids are also implicated in myelin formation and serve as bioactive molecules and energy substrates [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%